Plant Cyclin-Dependent Kinase Inhibitors of the KRP Family: Potent Inhibitors of Root-Knot Nematode Feeding Sites in Plant Roots - Vieira, Paulo; de Almeida Engler, Janice (Frontiers in Plant Science, 2017)
Root-knot nematodes (RKN), Meloidogyne spp., are distributed worldwide and impose severe economic damage to many agronomically important crops. The plant cell cycle machinery is considered one of the pivotal components for the formation of nematode feeding sites or galls. These feeding sites contain five to nine hypertrophied giant cells resulting from developmental reprogramming of host root cells by this pathogen. Giant cells undergo synchronous waves of mitotic activity uncoupled from cytokinesis giving rise to large multinucleate cells. As development of the nematode feeding site progresses, multiple rounds of DNA synthesis occur in the nuclei of giant cells, coupled with nuclear and cellular expansion. These cells are highly metabolically active and provide the nematode with nutrients necessary for its development and completion of its life cycle. In Arabidopsis seven cyclin dependent kinase inhibitors (CKIs) belonging to the interactors/inhibitors of the cyclin dependent kinases (ICK) family, also referred as Kip-Related Proteins (KRP) have been identified. Interactions of KRPs with CDK/Cyclin complexes decrease CDK activity, affecting both cell cycle progression and DNA content in a concentration-dependent manner. We performed the functional analysis of all Arabidopsis KRP gene members during RKN interaction in Arabidopsis to obtain more insight into their role during gall development. We demonstrated that three members of this family (KRP2, KRP5 and KRP6) were highly expressed in galls and were important for cell cycle regulation during nematode feeding site (NFS) development as shown by their different modes of action. We also pointed out that cell cycle inhibition through overexpression of all members of the KRP family can affect NFS development and consequently compromise the nematode’s life cycle. In this review we summarized our recent understanding of the KRP family of genes, and their role in controlling cell cycle progression at the RKN feeding site.